REINTEGRASI PENDIDIKAN INDONESIA MELALUI PEMIKIRAN DAN GERAKAN FETHULLAH GULEN - Muhammad Fahmi Hidayatullah (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
Abstract In the context of reform, it can be learned from the history of influential figures in each country in the world. Call it Fethullah Gulen, one of the most influential Muslim figures in Turkey. There is something interesting about the movement, namely hizmet (service). The movement model is used in education and the results provide progress and change the mindset of Islamic education institutions in the world. In addition, he also offers ideas through the learning experiences he has undertaken, so as to produce a balance of thinking between the life aspects of the world and the hereafter. This balance of thinking is encapsulated in the concept of the Fethullah Gulen movement in the field of Education.. Keywords: reintegration, indonesian education, fethullah gulen movement